Perception of the IGVGD programme participants on the effects of the programme on socioeconomic and nutritional well-being - Tarannum, Sabah; Ahmed, Farid; Hyder, SM Ziauddin (BRAC Research and Evaluation Division (RED), 2019)
Income Generation for the Vulnerable Group Development (IGVGD) Program is one of the main development initiatives of BR.A..C targeted to the poorest rural women. The IGVGD programme was launched in 1987 in collaboration with the World Food Programme (WFP) and the Government of Bangladesh. The Programme includes activities such as credit, savings, training, poultry rearing, health and nutrition education, and general awareness. The major objective of the programme is to increase real income of the rural destitute women through high yield variety (H1:'V) poultry rearing and other income generating activities. The objectives of this study are to examine the perception of the programme participants on the impact of the IGVGD programme on nutritional status particularly of the women and children as well as the perception of the IGVGDP women on their well-being. Data were collected through focus group discussions (FGDs). Six villages of Tangail thana were randomly selected and 6 FGDs were conducted with IGVGDP participants in September and October 1995. j_,fajor issues discussed during the FGDs were: training of the poultry workers and key rearers, credit schemes for poultry rearing, vaccine/drugs, issue-based meetings, wheat distribution food availability, control over household resomces, women's status within the household and community, health and nutritional status and the sanitary conditions of the households. The study revealed that the participating women had a great deal of interest in poultry rearing because the technology was traditionally known to them which could also integTate with their normal household activities. Poultry workers had many responsibilities to prevent poultry mortality and they were highly respected by the villagers. Majority of the women were economically self-supportive and they vvere not dependent on the male members for poultry rearing. They could improve the socioeconomic conditions through skill development training and other awareness programmes. Most IGVGDP women came to know about the common diseases (diarrhoea. common cold, nightblindness, anaemia, etc.) through attending the bimonthly issue-based meetings. The study also shows that the participating women were more conscious about health and nulrition-related issues and problems. The study further reveals that the women's mobility such as day to day contact with local Union Parishad . 40 u members and the development workers had been increased. They could gradually overcome the problems which restricted their involvement into development activities and their attitudes had begun to change. The IGVGD programme reached the target population successfully and helped improve their socioeconomic conditions and nutritional status.